The Construction of an Identity into 19th Century Argentinian Texts: Peregrinación de Luz del Día by J.B. Alberdi and Argirópolis by D. F. Sarmiento. (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
This paper treats the discursive relationship between utopian ideals and the philosophical Concepts found in other words such as Domingo Faustino Sarmiento and Juan Bautista Alberdi that may have contributed to the rise of an Argentinian culture in the 19th century.  it analyses texts by these two writers that illustrate the discursive Crossroads between essay and fiction as well as the pursuit of identity profiles.